Penerapan Framework Scrum Dalam Perancangan Sistem Pengelolaan Member Sport44 Gym - Waralungli, Julang; Santi, Nirma Ceisa (Al-Mantiq, 2025)
This research discusses the design of a digital-based member management system using the Scrum framework at Sport44 Gym, a fitness center located in Bojonegoro. The problem arises from the manual management of member data, class schedules, financial transactions, and supplement sales, which often leads to inefficiencies and data errors. This study aims to provide an integrated and interactive solution through a system that supports online registration, membership renewal, schedule access, payments, and supplement purchases via mobile and web platforms. Using the Scrum method, development was carried out in several sprints, with continuous User feedback and improvements at each stage. The tools used in system design included UML, Figma for UI/UX design, and Useberry for usability testing. The final result is a functional prototype that enhances User experience and supports better operational efficiency at Sport44 Gym.